1. RADIOFREQUENCY ABLATION OF THE CELIAC PLEXUS FOR THE TREATMENT OF UPPER ABDOMINAL CANCER PAIN (Vietnam Journal of Community Medicine, 2025)
In this report, we present two cases of patients with upper abdominal cancer. Case 1: A 68-year-old male patient with liver cancer metastasis to the stomach and pancreatic metastasis. Case 2: A 48-year-old male patient with esophageal cancer metastasis to the liver and pancreas. Both patients did not respond to conventional analgesics, NSAIDs analgesics were used in combination with Opioids, but the patients still had severe pain. The VAS pain score was always 9/10. We performed radiofrequency ablation of the celiac plexus, which significantly reduced the patient's pain level immediately afterwards without any complications. Case 1: The patient was followed up with lasting pain relief after 9 months with a VAS score of 2/10. Case 2: The patient was followed up with lasting pain relief after 5 months with a VAS score of 1/10 and the patient was able to return to normal daily activities. Radiofrequency ablation of the celiac plexus is a safe, effective method that can provide long-term pain relief for patients with upper abdominal cancer.
Keywords: Celiac plexus; upper abdominal cancer; radiofrequency; pain.